2023
DOI: 10.1002/pat.5977
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and properties of flame retardant biobased polyamide elastomer with shape memory

Abstract: Nylon is the general name of high molecular polymers with amide bonds repeat structure in the main chain. Because of its good wear resistance, excellent chemical resistance and outstanding impact resistance, it is widely used in various fields of national life, such as automobile parts, oil pipelines, electronic parts, gears, connectors, coating materials and medical applications. Using isocyanate terminated polyamide prepolymer as hard segment, polypropylene glycol as soft segment and triethanolamine as cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Synthesis and properties of IAHDP: (a, b) The synthesis of BTPAE, (c) the tensile property of BTPAE, and (d) the flame-retardant mechanism. [Reprinted with permission from ref . Copyright 2023, Wiley.…”
Section: Applications Of Btpaesmentioning
confidence: 99%
See 1 more Smart Citation
“…Synthesis and properties of IAHDP: (a, b) The synthesis of BTPAE, (c) the tensile property of BTPAE, and (d) the flame-retardant mechanism. [Reprinted with permission from ref . Copyright 2023, Wiley.…”
Section: Applications Of Btpaesmentioning
confidence: 99%
“…Gao et al prepared a class of BTPAEs with flame-retardant functions. The specific synthesis is shown in Figures a and b, and the obtained material is named IAHDP- x {where x denotes the content of (9,10-dihydro9-oxa-10-[ N , N -bis­(2-hydroxyethylamino methylene)]-10-phenanthroline-10-oxide) (DDP) in the polymer}.…”
Section: Applications Of Btpaesmentioning
confidence: 99%
“…Furthermore, under dicyandiamide catalysis, the phosphonic acid group forms phosphonic anhydride, which then reacts with hydroxyl groups on the cellulose molecule to generate numerous P-O-C covalent bonds by directly grafting onto the cellulose fiber to produce phosphate cellulose, imparting efficient flame retardancy and durability [18]. Triethanolamine is used in the production of flame retardants as a crosslinking agent [19]. It is also reported that mono-, di-, and triethanolamine inhibit the growth of a variety of microorganisms [20,21].…”
Section: Introductionmentioning
confidence: 99%